Supplementing Intraoperative Mastoidectomy Teaching With Video-Based Coaching. (April 2023) - Raymond, Mallory; Studer, Matthew; Al-Mulki, Kareem
Objectives: Video-based coaching might complement general surgery education, but little is known of its applicability for otologic microsurgical teaching. Our purpose was thus to evaluate the content and resident-perceived benefit of video-based coaching for mastoidectomy education. Methods: In this mixed-methods pilot design, mastoidectomies were recorded from operative microscopes and reviewed during 30-minute video-based coaching sessions at 2 tertiary care centers. Eight residents and 3 attendings participated. Ten-point Likert-type questionnaires on the extent to which attendings taught 12 topics through 8 techniques were completed by residents after surgical and coaching sessions. Coaching sessions and structured interviews with residents were audio-recorded, transcribed and iteratively coded. Results: Seven audio-recordings were available for coaching sessions, during which a mean of 2.22 ± 0.5 topics per minute were discussed. Of the 12 teaching topics, technique was discussed most frequently (32%, 0.71 ± 0.2 topics/min), followed by anatomy (16%, 0.31 ± 0.16 topics/min). Of all 8 ratings between coaching and operative sessions, residents indicated a greater extent of discussion of anatomy (median difference, [95% confidence interval (CI)] of 3 [1-4]), progress (2.25 [95% CI, 0.5-4]), technique (3.5 [95% CI, 1.5-5.5]), pitfalls (2.5 [95% CI, 1-3.5]), and summarizing (3 [95% CI, 1-5]). In structured interviews, residents reported improved self-confidence and global perspective. Conclusions: Video-based coaching is educationally dense and characterized by perceived richer teaching and promotion of a deeper surgical understanding. It requires no additional resources, can be completed in a short period of time and can be implemented programmatically for any otolaryngologic subspecialty utilizing video-recording capable equipment.